Effect of surface states on the electrical and optical characteristics of InP MIS capacitor - Chakrabarti P.; Madheswaran M.; Mishra B.K.; Singatwaria S.; Tandon A.; Ghosh B. (My University, 2025)
The effect of surface states on the electrical and optical characteristics of an InP metal-inulator-semiconductor (MIS) capacitor has been studied theoretically. The semi-numerical model presented here examines the potential of the device for optically controlled applications. While the device shows much promise for use as a voltage variable and/or optically controlled capacitor, its performance is seriously limited by the property of the interface between InP crystal and insulator film (Al2O3, in this case), where a considerable number of surface states exist with their energy distribution widely spread throughout the crystal forbidden gap.